#### Answer

$r'(s) = 3s^{2} - 4s$

#### Work Step by Step

$r(s) = s^{3} -2s^{2} +3$
Therefore,
$r'(s) = 3s^{3-1} - 2(2)s^{2-1} +0$
$r'(s) = 3s^{2} - 4s$

Published by
Pearson

ISBN 10:
0321999584

ISBN 13:
978-0-32199-958-0

$r'(s) = 3s^{2} - 4s$

$r(s) = s^{3} -2s^{2} +3$
Therefore,
$r'(s) = 3s^{3-1} - 2(2)s^{2-1} +0$
$r'(s) = 3s^{2} - 4s$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.